1999
DOI: 10.1093/jnci/91.20.1751
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fat and Protein in Relation to Risk of Non-Hodgkin's Lymphoma Among Women

Abstract: Greater dietary intake of certain meats and fats was associated with a higher risk of non-Hodgkin's lymphoma. These relationships and their potential mechanisms deserve further examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

19
133
4

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(157 citation statements)
references
References 26 publications
19
133
4
Order By: Relevance
“…15 In addition, an American cohort study following women for 14 years did not report any association between tobacco smoking and the development of NHL overall. 12 Nevertheless, our analyses for specific histological subtypes failed to confirm the association between smoking and follicular NHL recently reported by Interlymph 48 and also found in 3 cohort studies carried out in USA 7,10 and in Sweden. 5 The link between smoking and follicular NHL was biologically plausible, as the carcinogenic components of cigarette smoke should increase the frequency of the common translocation for follicular NHL, which leads to the persistent expression of the anti-apoptosis gene BCL2.…”
Section: Discussioncontrasting
confidence: 65%
“…15 In addition, an American cohort study following women for 14 years did not report any association between tobacco smoking and the development of NHL overall. 12 Nevertheless, our analyses for specific histological subtypes failed to confirm the association between smoking and follicular NHL recently reported by Interlymph 48 and also found in 3 cohort studies carried out in USA 7,10 and in Sweden. 5 The link between smoking and follicular NHL was biologically plausible, as the carcinogenic components of cigarette smoke should increase the frequency of the common translocation for follicular NHL, which leads to the persistent expression of the anti-apoptosis gene BCL2.…”
Section: Discussioncontrasting
confidence: 65%
“…If weight gain in early adulthood is not responsible, our results could instead suggest that obesity from childhood is a risk factor for NHL. It seems unlikely however that nutrition during childhood, linked to adult stature (Silventoinen, 2003), increases NHL risk, since generally little evidence of an association with height has been presented either here or elsewhere (Whittemore et al, 1985;La Vecchia et al, 1990;Zhang et al, 1999;Cerhan et al, 2002). Alternatively, it may be that an underlying genetic component of obesity is involved in the pathogenesis of NHL.…”
Section: Discussionmentioning
confidence: 81%
“…Accordingly, it has been suggested that anthropometric measures, reflecting the degree of adiposity, as well as polymorphisms in genes associated with energy homeostasis such as leptin (LEP), leptin receptor (LEPR) and adiponectin (APM1), may increase NHL risk. However, while positive associations have been reported between NHL and anthropometric characteristics (Holly et al, 1999;Calle et al, 2003;Bahl et al, 2004;Pan et al, 2004), others have not (Paffenbarger Jr et al, 1978;Whittemore et al, 1985;Franceschi et al, 1989;La Vecchia et al, 1990;Zhang et al, 1999;Cerhan et al, 2002;Chang et al, 2005). Furthermore, polymorphisms in the LEP (an A to G nucleotide (nt) change at position 19 in the 5 0 -untranslated region (Hager et al, 1998), and a G to A substitution at nt À2548 upstream of the ATG start site (Mammes et al, 1998)) and LEPR (an A to G transition at nt 668 from the start codon that converts glutamine to arginine at codon 223 (223Q4R) (Gotoda et al, 1997)) genes were recently shown to modulate NHL risk (Skibola et al, 2004).…”
mentioning
confidence: 98%
“…Significant and nonsignificant positive associations, ranging between 1.1 and 1.76, for the highest versus lowest category of total fat intake have been reported in case-control and cohort studies. 384,385,[401][402][403] Findings by dietary fat subgroups have been heterogeneous; however, significant and nonsignificant elevated relative risks have been reported for saturated fats. 384,385,395,[401][402][403] Some studies have reported positive associations 385,402-404 and significant dose-response relationships 385 with animal protein, whereas other studies have not.…”
Section: Dietary Factorsmentioning
confidence: 99%
“…384,385,[401][402][403] Findings by dietary fat subgroups have been heterogeneous; however, significant and nonsignificant elevated relative risks have been reported for saturated fats. 384,385,395,[401][402][403] Some studies have reported positive associations 385,402-404 and significant dose-response relationships 385 with animal protein, whereas other studies have not. 384,405 In one casecontrol study, a significant inverse association was found with the highest compared with lowest quartile of protein from animal sources (OR 5 0.39, 95% CI: 0.22-0.70).…”
Section: Dietary Factorsmentioning
confidence: 99%